2010
DOI: 10.1371/journal.pone.0009100
|View full text |Cite
|
Sign up to set email alerts
|

Step Process for Selecting and Testing Surrogates and Indicators of Afrotemperate Forest Invertebrate Diversity

Abstract: BackgroundThe diversity and complexity of invertebrate communities usually result in their exclusion from conservation activities. Here we provide a step process for assessing predominantly ground-dwelling Afrotemperate forest invertebrates' (earthworms, centipedes, millipedes, ants, molluscs) potential as surrogates for conservation and indicators for monitoring. We also evaluated sampling methods (soil and litter samples, pitfall traps, active searching quadrats and tree beating) and temporal (seasonal) effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 44 publications
1
13
0
Order By: Relevance
“…To date, however, no regional study has investigated the direct impact of invasive earthworms on native plant or animal communities, although some Fig. 7.2 Distribution map of alien earthworms in South Africa (map produced by R. Leihy using data from Janion-Scheepers et al 2016) invasive species have been found in native forest ecosystems (Uys et al 2010;Nxele 2012).…”
Section: Composition Of the Known Alien Terrestrial Invertebrate Faunamentioning
confidence: 99%
“…To date, however, no regional study has investigated the direct impact of invasive earthworms on native plant or animal communities, although some Fig. 7.2 Distribution map of alien earthworms in South Africa (map produced by R. Leihy using data from Janion-Scheepers et al 2016) invasive species have been found in native forest ecosystems (Uys et al 2010;Nxele 2012).…”
Section: Composition Of the Known Alien Terrestrial Invertebrate Faunamentioning
confidence: 99%
“…The bee and true bug richness is likely to be higher if sampling was repeated at different times of the year, but the molluscs do not show much temporal turnover (Uys, Hamer & Slotow 2010), and the richness value for molluscs is unlikely to increase much with additional sampling.…”
Section: Assessment Of Diversity or Species Richnessmentioning
confidence: 99%
“…However, to date there still remains no consensus amongst researchers of the criteria for selecting appropriate surrogates, despite the attention that this topic has received in recent research (e.g. Heino & Soininen, 2007;Lovell et al, 2007;Williams et al, 2007;Uys et al, 2010). Two recent studies of invertebrates in South Africa provide useful examples of the development of surrogate use.…”
Section: Surrogacymentioning
confidence: 99%